Theranostic nanoparticles with tumor-specific enzyme-triggered size reduction and drug release to perform photothermal therapy for breast cancer treatment - Rui Liu; Chuan Hu; Yuanyuan Yang; Jingqing Zhang; Huile Gao (Elsevier, 2019)
Although progress has been indeed made by nanomedicines, their efficacies for cancer treatment remain low, consequently leading to failures in translation to clinic. To improve the drug delivery efficiency, nanoparticles need to change size so as to fully utilize the enhanced permeability and retention (EPR) effect of solid tumor, which is the golden principle of nanoparticles used for cancer treatment. Herein, we employed cationic small-sized red emission bovine serum albumin (BSA) protected gold nanocluster (AuNC@CBSA, 21.06 nm) to both load indocyanine green (ICG) and act as imaging probe to realize theranostic. Then AuNC@CBSA-ICG was fabricated with negatively charged hyaluronic acid (HA) to form AuNC@CBSA-ICG@HA, which was about 200 nm to easily retain at tumor site and could be degraded by tumor-specific hyaluronidase into small nanoparticles for deep tumor penetration. The HA shell also endowed AuNC@CBSA-ICG@HA with actively targeting ability and hyaluronidase-dependent drug release. Furthermore, the quenching and recovery of fluorescence revealed the interaction between ICG and carrier, which was essential for the investigation of pharmacokinetic profiles. No matter in vitro or in vivo, AuNC@CBSA-ICG@HA showed markedly anti-tumor effect, and could suppress 95.0% of tumor growth on mice breast cancer model. All results demonstrated AuNC@CBSA-ICG@HA was potential for breast cancer therapy. KEY WORDS: Size-shrinkage, Drug release, Photothermal therapy, Theranostic, Breast cancer